Inclusive access to emergency services: an action research project focused on hearing-impaired citizens - Constantinou, Vaso; Ioannou, Andri; Diaz, Paloma (My University, 2017)
In case of emergency, hearing-impaired people are not always able to access emergency services, and hence, they do not have equal access to social support and infrastructure. In this work, we describe an action research study that undertakes the development and evaluation of a system aiming to meet the communication needs of hearing-impaired citizens in cases of emergency. The system consists of (1) a mobile application that records and sends the details of an emergency event and (2) a central management system that handles these calls from the operation center at the emergency services. The system was completed in four cycles of design, development and evaluation with the involvement of 74 hearing-impaired users and three officers from the Cyprus Police (Emergency Response Unit). Results demonstrated how the system can provide easy and direct access to emergency services, without the need of any intermediate, enabling the inclusion of these citizens in a critical process such as the response to an emergency.
Keywords: Technology for hearing-impaired people; Inclusive citizen participation; Inclusive design; Action research; Emergency services